Performance Evaluation of Sensor Node Scalability on Reactive Modified I-Leach Protocol - Singh, Jagwant; Singh, Jaswinder (International Journal of Computer Sciences and Engineering, 2025)
Sensor nodes in Wireless Sensor Networks having restricted power, weak computing capacity and reduced storage capacity. Therefore an proficient energy saving method is required to extend the duration of a network. LEACH is one of the popular algorithm, but it's some negatives such as for example each node may possibly not be established often in clusters, even though nodes have different power, CH is selected unreasonably and many other. These limitations are over come in I-LEACH algorithm by which sensor node with higher remaining power, more neighbors and lesser range from Base station is selected as a Cluster Head. I-LEACH algorithm more could be revised and thereby we could reduce the energy consumption of the network. Thus it's be great for prolonging the network lifetime. This research paper has dedicated to increasing the network lifetime by using the reactive I-LEACH protocol. The comparison among LEACH, I-LEACH and proposed method has also been performed based on power usage and network life time. Even in case of node scalability analysis the proposed technique shows rather effective results.